2010
DOI: 10.1590/s0101-31222010000200012
|View full text |Cite
|
Sign up to set email alerts
|

Teste de envelhecimento acelerado para avaliação do potencial fisiológico de sementes de grama-bermuda

Abstract: TESTE DE ENVELHECIMENTO ACELERADO PARA AVALIAÇÃO DO POTENCIAL FISIOLÓGICO DE SEMENTES DE GRAMA-BERMUDA 1RESUMO -A utilização de sementes para formação de gramados esportivos e ornamentais tem assumido grande importância no Brasil, principalmente pelo baixo custo em relação à formação por placas de tapetes naturais. As "bermudas" [Cynodon dactylon (L.) Pers] são as principais gramas utilizadas na formação de campos esportivos e, dentre os problemas enfrentados, destacase a dificuldade de estabelecimento adequad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
1
5
0
1
Order By: Relevance
“…The water content analyses of the seeds, after the accelerated aging period with saturated solution (11% NaCl) and saturated saline solution (40% NaCl), presented lower results in comparison with the traditional methodology. These results were also observed in seeds of similar size by Silva et al (2010), in bermuda-grass seeds (Cynodon dactylon), and by Radke et al (2016), in coriander seeds (Coriandrum sativum).…”
Section: Resultssupporting
confidence: 64%
“…The water content analyses of the seeds, after the accelerated aging period with saturated solution (11% NaCl) and saturated saline solution (40% NaCl), presented lower results in comparison with the traditional methodology. These results were also observed in seeds of similar size by Silva et al (2010), in bermuda-grass seeds (Cynodon dactylon), and by Radke et al (2016), in coriander seeds (Coriandrum sativum).…”
Section: Resultssupporting
confidence: 64%
“…Esse é um requisito importante para realização de testes de vigor, pois para obtenção de resultados consistentes é necessário que o grau de umidade dos lotes esteja padronizado e não ultrapasse 2% de diferença (Silva et al, 2010), e deve estar abaixo de 13% para evitar deterioração das sementes durante o armazenamento (Guareschi et al, 2015).…”
Section: Resultsunclassified
“…The accelerated aging test provides conditions that can cause the anticipated deterioration of the physiological processes of seeds resulting in the loss of germinative viability, simulating conditions of storage by long periods (SILVA et al, 2010). The exposure of celosia seeds to high humidity and temperature for different periods of heat demonstrated that these species can be stored by long periods without losing the viability.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the accelerated aging test, which uses high temperatures and elevated relative humidity of air, for a period of time, what provokes deleterious effects in seeds because it triggers and intensify their metabolic activities (MARCOS-FILHO, 2015). The efficiency of this test allows, also, evaluating the storage potential of seeds, because the difference presented by the same when submitted to the aging test indicate their sensibility to deterioration (MENEZES et al, 2008;SILVA et al, 2010).…”
Section: Introductionmentioning
confidence: 99%